EFFECTS OF TRANSACTIONAL ANALYSIS AND SELF-EFFICACY STRATEGIES ON EMOTIONAL LABOUR OF NURSES IN ILORIN, KWARA STATE, NIGERIA
Some nurses have been perceived to have poor interpersonal relationships with patients. This, could affect their productivity and also inhibit psychological torture and wellness of patients. Thus, nurses require emotional labour to overcome these challenges. Emotional labour is the degree of one‟s display of appropriate emotion in response to the patient and the management of feelings to create a publicly observable emotional display as the situation demands. Transactional Analysis and Self-Efficacy Strategy treatments have been employed in enhancing the emotional labour of sales personnel, cashiers, receptionists, police officers and some healthcare personnel but have not been used in respect of nurses‟ professional output. Therefore, this study investigated effects of TA and SES on emotional labour of nurses in the government hospitals Ilorin, Kwara State, Nigeria. The study employed a pretest-posttest, control group, quasi-experimental design with a 3x3x2 factorial matrix. Simple random sampling technique was used to select 124 nurses from University of Ilorin Teaching Hospital and Civil Service Hospital in Kwara State, these hospitals are government hospitals. Two instruments were used. They are Emotional Labour Scale (=0.81) and Emotional Intelligence Scale (=0.80). The samples were randomised into two experimental groups and one control group. It involves eight weeks training; one hour daily contact session twice a week for the experimental groups while the control group was met in the first and eighth week of the contact period. The groups are Transactional Analysis, Selfefficacy and Control group. Seven hypotheses were tested at the 0.05 level of significance. Data were analysed using the descriptive statistics and analysis of covariance. There was a significant main effect of treatments on emotional labour of participants (F(2,114)=44,487, p<0.05). The Transactional Analysis group obtained the highest mean score in emotional labour ( X =170.286), Self-efficacy mean score ( X =164.77), and the lowest mean score obtained by the control group ( X =136.571) which means that Transactional Analysis was more effective in enhancing the emotional labour of the participants. There was no significant difference in the two-way interaction effect of treatment and the moderating variable of emotional intelligence emotional intelligence on participants‟ emotional labour. A comparison of the emotional labour scores of the participants with low, moderate and high levels of emotional intelligence treated with Transactional Analysis and Self-Efficacy strategies were not also significant. Although Transactional Analysis was more effective than Self-Efficacy Strategies, the two approaches were effective in enhancing emotional labour of nurses in Kwara State. The two intervention strategies are, therefore, recommended for use by nurses and other helping professionals in handling interpersonal relationships with their clients.